The English Radical Whig Origins of American Constitutionalism - David N. Mayer (Washington University Law Quarterly, 1992)
Scholars-at first historians and political scientists, and more recently legal scholars-who have become more enamored with the civic republican implications of early American thought have overlooked the "whig" basis of that thought. As a result, much recent scholarship about early American constitutionalism has been seriously misguided.
Keywords: Constitutional history -- United States